The Impact of Monetary Strategies on Inflation Persistence - Evžen Kocenda; Balázs Varga (Center for Economic Studies and ifo Institute (CESifo), 2017)
We analyze the impact of price stability-oriented monetary strategies (inflation targeting—IT—and constraining exchange rate arrangements) on inflation persistence using a time-varying coefficients framework in a panel of 68 countries (1993–2013). We show that explicit IT has a stronger effect on taming inflation persistence than implicit IT and is effective even during and after the financial crisis. We also show that once a country hits the ZLB its inflation persistence mildly decreases and that there exists a mild pull to return to inflation persistence mean once a central bank moves away from its inflation target. The link between inflation persistence and constraining exchange rate regimes is less pronounced than that of IT and regimes with the U.S. dollar as a reserve currency are less effective than those using the Euro (Deutsche mark). On other hand, the U.S. persistence transers disproportionately lower effect on other countries' persistence than the IP of Germany.
Keywords: C22; C32; E31; E52; F31; 330; inflation persistence; inflation targeting; exchange rate regime; flexible least squares